Analysis Of The Needs For Health Human Resources Competence Development Through Education And Training At The Pinangsori Health Center Pinangsori District Tapanuli Central District Year 2020 - Johannes Sembiring (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
The minimum condition that is expected to the activities in health centers can be carried out properly, one of them is the health personnel that is fulfilled as stated at Regulation of Health Department No. 75 of 2014, but the number of health worker at the health center is not currently in accordance with the minimum standard of labor in Regulation of Health Department, so the service at the health center is less optimal and there are multiple tasks. The purpose of the research was to analyze the state of competence of health workers and to analyze the need for competency development of health human resources through education and training at Pinangsori Health Center. This research is descriptive with a qualitative approach in determining the need for competency development for health workers in the health center. Methods of data collection used observation and in-depth interviews. The need result analysis of the health worker shows that there are 2 people who have competence based on administrator health to Regulation of Health Department number 75 of 2014. The result of the need analysis of competency for development shows that most of health workers who have high school degree need higher education at least Diploma III. On the job training such as guidance and discussion is required by health workers. Apart from that, off the job training is also needed such as emergency training (PTC, ATLS or GELS and PONED) is also required by the doctor; PPGDON training, CTU, Hypnobirthing, BBLR management is required by the midwife; BTCLS training, Nursing Communication and Ethics is required by the nurse. The recommendation of the research is to apply the needs to competency developing health through education and training in the other health centers and the availability of good information system of the workforce so that it can be a reference to take a policy in the planning of health manpower need and its development.